Nitrogen released from sago pulp waste and Gliricidia sepium pruning mixtures on a Dystrudept of Central Moluccas and its effect on the growth of maize - June Annethe Putinella; Yulia Nuraini; Budi Prasetya (Brawijaya University, 2022)
The agricultural sector is the mainstay of the economy in Central Moluccas. However, most agricultural soils on the island have low soil fertility. One of the efforts that farmers can make to improve soil fertility is to apply organic matter, which is widely found in Central Moluccas. This study aimed at elucidating the effect of mixing high-quality organic material (Glicidia sepium pruning) with low-quality organic material (sago pulp waste) on the improvement of available nitrogen in an acid soil (Dystrudept) and growth of maize. Two experiments were carried out in a laboratory and a greenhouse. The compositions of the mixtures of sago pulp waste (A) and pruning of Gliricidia sepium (G) were A0 G100; A20G80; A40G60; A60G40; A80G20, and A100G0. Six treatments and one control (no application of residues) were arranged in a completely randomized design. The results showed that the application of the mixture of 20% and 80% of Gliricidia sepium pruning (A20G80) increased the cumulative amount of mineral N in the soil higher than that of the other organic material mixtures, which in turn improved maize growth.